Exploring the Immersive Potential of Accessibility Options for Deaf and Hard-of-Hearing Players - Pigulak, Joanna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2025)
This study examines the implementation and effectiveness of accessibility options in digital games, focusing on their role in shaping immersive experiences for deaf and hard-of-hearing players. Using a mixed-methods approach, this research combines game design analysis and qualitative interviews with deaf and hard-of-hearing users, focusing particularly on Polish video games. The findings reveal that text transcription, visual indicators, and haptic feedback significantly influence player engagement, yet their inconsistent implementation often disrupts immersion. By addressing the challenges faced by hard-of-hearing players, this study contributes to the broader discourse on inclusive game design and the artistic potential of accessibility solutions.